Solve the differential equation given by
(3x + 2y + y^2)dx + (x+4xy+5y^2)dy=0
"\\dfrac{\\partial Q}{\\partial x}\\not=\\dfrac{\\partial P}{\\partial y}"
"\\mu=x+y^2"
"(x+y^2)(3x + 2y + y^2)dx"
"+ (x+y^2)(x+4xy+5y^2)dy=0"
"P=3x^2+2xy+xy^2+3xy^2+2y^3+y^4"
"\\dfrac{\\partial P}{\\partial y}=2x+8xy+6y^2+4y^3"
"Q=x^2+4x^2y+5xy^2+xy^2+4xy^3+5y^4"
"\\dfrac{\\partial Q}{\\partial x}=2x+8xy+6y^2+4y^3"
"\\dfrac{\\partial P}{\\partial y}=\\dfrac{\\partial Q}{\\partial x}"
"\\dfrac{\\partial u}{\\partial x}=3x^2+2xy+4xy^2+2y^3+y^4"
Integrate
Then
"\\dfrac{\\partial u}{\\partial y}=x^2+4x^2y+6xy^2+4xy^3+\\varphi'(y)""=Q=x^2+4x^2y+6xy^2+4xy^3+5y^4"
"\\varphi'(y)=5y^4"
"\\varphi(y)=y^5+C"
The original differential equation has the following solution
Comments
Leave a comment